Using behavior change approaches to improve complementary feeding practices. (15th October 2017) - Sanghvi, Tina; Seidel, Renata; Baker, Jean; Jimerson, Ann
Abstract: This paper applies an implementation framework, based on a behavior change model, to compare four case studies of complementary feeding programs. It aims to expand our understanding of how to design and implement behavior change interventions aimed at improving complementary feeding practices. Four programs met the selection criteria of scale and documented improvements: Bangladesh, Malawi, Peru, and Zambia. We examined commonalities and differences in the design and implementation of social and behavior change approaches, use of program delivery platforms, challenges encountered, and lessons learned. We conclude that complementary feeding practices, in particular dietary diversity, can be improved rapidly in a variety of settings using available program platforms if interventions focus on specific constraints to food access and use effective strategies to encourage caregivers to prepare and feed appropriate foods. A five‐step process is presented that can be applied across a range of complementary feeding programs to strengthen their impacts.